Educación ambiental de niños y niñas y su influencia en la calidad del paisaje de la Escuela “Jose Peralta”, sitio Facundo, Flavio Alfaro - Ozaeta Bermúdez, Gabriela Stefany (2019)
This research aimed to evaluate the influence of Environmental Education on the quality of the environment of the "José Peralta" school, site Facundo, Flavio Alfaro. The research was qualitative. Techniques such as observations, training, active learning, matrix of evaluation indicators of educational institutions and statistical tests were applied. The first phase of the study that involves determining the level of environmental education; This included: visits to the study area, collection of general study data, identification of the participants' initial environmental motivations and evaluation of the initial environmental knowledge. In the second phase the quality of the school landscape was determined through environmental quality criteria according to the school environment. Finally, the third phase includes the development of an environmental education program, based on quality indicators of the school environment of the "José Peralta" unit to assess the knowledge and quality of the post-program environment. It was found that the predominant children found an acceptable motivation (32,9%). However, an average score of 4,53 / 10 points is required in the initial written assessment that amounted to 8,66 post-program points. It is concluded that there is a direct relationship between the level of environmental education and the quality of the school environment.